Concepts for today - Smith, Lorraine C.; Mare, Nancy Nici, 1957-; Cable News Network (Boston, Mass. : Thomson/Heinle, 2004)
These best-selling, academic skills texts systematically develop students' reading and vocabulary skills through engaging themes and intensive practice. Students learn successful reading strategies and are further prompted to build proficiency in their writing, listening, and speaking skills.
The Paradox of Happiness -- Cose to Home: Technologica Advances -- The Birth-Order Myth -- hy So Many More AmericansDie in Fres -- Acupuncture: The New Od Medicine -- Hghs and Lowsin Sel-Esteem -- The Federal System of overnment -- Too Soon Od, Too Late ise -- The Pursuit of Excele -- Antarctca: hose Continent is t Anyway? -- A Messenger from the Past -- Is Ti meTravel Possible?
Each unit includes optional activities available via CNN video clips and InfoTrac college edition, the online library.
Includes bibliographical references (p. iv) and indexes.
1
Keywords: English language -- Textbooks for foreign speakers; Reading (Secondary) -- Problems, exercises, etc